Social climate of nursing service and nurses' commitment in hospitals of Mountain Province - Tampican, Elena Benbenen- 1948
The purpose of this study was to identify the social climate existing in the nursing service and the nurses' commitment to organization and job in six hospitals of Mountain Province. Specifically, the investigator sought to answer the following questions:1. What is the social climate that pervades in the nursing service as perceived by the staff nurses and supervisors along these two dimensions?1.1. Relationship Dimension1.2. Supervisor's Behavior as a leader2. What is the extent of nurses' commitment to their organization and job?3. Is there a relationship between open social climate and nurses' commitment to their organization and job?4. Is the social climate and nurses' commitment significantly associated with the following variables?4.1. Nurses' Demographic data4.1.1. Age4.1.2. Position4.1.3. Length of Service4.1.4. Educational Attainment4.1.5. Civil Status4.2 Hospital Data4.2.1 Location4.2.2 Bed CapacityTo answer these questions, a research was conducted in six hospitals in the Mountain Province. Eighty four (84) nurses, both supervisors and staff nurses, were the respondents of the questionnaire on social climate and commitment to organization and job.The independent variables in this study was open social climate; with nurses' commitment to organization and job as the dependent variable, and nurses' demographic and hospital data as the intervening variables.Descriptive statistics were used to provide information about the nurses; frequencies and percentages were used to establish the profile of the respondents and the hospitals. Weighted mean was used to describe the social climate and commitment of nurses as perceived by nurses and supervisors. Inferential statistics such as Pearson's Product Moment Correlation and t-Test were used to provide information regarding the relationship between open social climate and commitment of nurses to organization and job. Chi-Square was used to describe the association between social climate and nurses' commitment and the selected variables.The results of the investigation revealed the following:1. The general social climate that pervades in the nursing service in six hospitals of Mountain Province tends to be open as indicated by the high mean scores of the relationship behaviors and supervisors' behavior as a leader.2. Nurses are highly committed to their organization and job.3. There was a significant relationship between an open social climate along collegial and intimate behaviors and commitment of nurses to organization.4. Findings of association between the social climate and nurses' commitment and the selected variables include:1.14.1. The intervening variable found to be significantly associated with social climate is civil status.4.2. Position is found to be significantly associated with commitment to organization.4.3. Variables found to be significantly associated with commitment to the job are position, educational attainment, civil status and location.In the light of the findings, it is recommended that nurse administrators be given guidelines for organizing and managing nursing service based on social climate along relationship dimension and supervisors' behavior. The collegiality, intimacy and supportive behavior has be expanded, strengthened and maintained as one moves on or face new challenges such as technological advances and development. Open social climate surfaced to be a very worthwhile intervention for the nurses' commitment to their organization and job in order to provide quality patient care.